Article Dari Kapital Simbolik menuju Pengembangan Destinasi: Analisis 4A terhadap Wisata Religi di Makam Abuya Syarwani, Indonesia - Adinda Sheika Salsabila Al-rigfah; Lukmanul Hakim; Nurbini; Dedy Susanto (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2026)
Religious tourism development is commonly assessed through infrastructure and managerial readiness, yet these perspectives do not fully explain why some pilgrimage sites continue to attract visitors despite weak facilities and informal governance. This article examines the Abuya Syarwani Tomb in Balikpapan, Indonesia, by integrating the 4A framework with Bourdieu’s concepts of habitus, symbolic capital, and field. Using a qualitative case study based on interviews, field observation, and document analysis, the study finds that the site’s main strength lies in symbolic attraction rooted in Abuya Syarwani’s religious authority, historical legacy, and the embedded habitus of pilgrimage. However, this strength has not been converted into adequate accessibility, amenities, or institutional support. Limited transport, weak signage, uneven facilities, and informal family-based management constrain destination development. The study argues that ancillary governance, rather than attraction alone, is the central bottleneck in pesantren-based religious tourism